Research on the Collaborative Cultivation Path of Students’ Kinesthetic and Emotional Cognition Through Dance Teaching from the Perspective of Multiple Intelligences - Zhang, Bi; Gang, Yi (Journal of Advanced Research in Education, 2025)
With the in-depth advancement of quality-oriented education, the role of dance teaching in fostering students’ comprehensive qualities has become increasingly prominent. Based on Gardner’s Theory of Multiple Intelligences, this study focuses on exploring the collaborative cultivation mechanism of dance teaching on students’ kinesthetic intelligence and emotional cognitive abilities. By combining literature analysis with teaching practice, it systematically sorts out the inherent connection between dance movement training and emotional experience, and reveals the promoting effect of physical movement expression on psychological development such as emotional perception and self-cognition. The study constructs a three-dimensional teaching model including body perception training, emotion-guided teaching, and creative choreography practice, emphasizing the stimulation of students’ physical expression potential through situational creation and improvisational performance. Practice shows that this teaching model can effectively improve students’ physical coordination, sense of rhythm, and emotional expression ability, while also playing a positive role in cultivating students’ sense of teamwork and aesthetic literacy. The research provides a theoretical basis for innovating art education methods and has practical significance for promoting the all-round development of students. In the future, further exploration can be made on differentiated cultivation strategies for students of different age groups.